Protection by Conformationally Restricted Mobility: First Solid-Phase Synthesis of Triostin A - Tulla-Puche, Judit; Marcucci, Eleonora; Fermin, Manuel; Bayó-Puxan, Núria; Albericio, Fernando (Chemistry : a European journal, 2008)
Conformationally restricted mobility: The application of an efficient solid‐phase strategy based on protection by conformationally restricted mobility (see scheme) has allowed, for the first time, the synthesis and determination of the biological activity of the two triostin A conformers, which result from the isomerization cis/trans of the N‐methyl group of Cys. The most polar conformer showed the greatest inhibitory effect on cell growth.